Views of Medical Educators and Intern Doctors on the Existing MBBS Curriculum (Bangladesh Journal of Medical Education, 2014)
This study was carried out to get an idea about the views of medical educators and intern doctors regarding the current undergraduate medical curriculum. A partially descriptive open ended questionnaire was distributed among teachers of all three phases and intern doctors in undergraduate curriculum in different public and private medical colleges in Bangladesh and was returned by 120 teachers and 663 intern doctors. Qualitative analysis of data was done. Among teachers 70% agreed to need for changes, 68.4% were in favor of present internship training system and 85% were against carry on system. But 94% and 51% of intern doctors were in favor of need changes of curriculum and present internship training respectively. 91% were against carry on system. DOI: http://dx.doi.org/10.3329/bjme.v3i1.18589 Bangladesh Journal of Medical Education Vol.3(1) 2012: 8-11